FBXW7 is involved in the acquisition of the malignant phenotype in epithelial ovarian tumors. Issue 10 (24th September 2016) - Kitade, Shoko; Onoyama, Ichiro; Kobayashi, Hiroaki; Yagi, Hiroshi; Yoshida, Sachiko; Kato, Masaya; Tsunematsu, Ryosuke; Asanoma, Kazuo; Sonoda, Kenzo; Wake, Norio; Hata, Kenichiro; Nakayama, Keiichi I.; et al.
Abstract : FBXW7 is a ubiquitin ligase that mediates ubiquitylation of oncoproteins, such as c‐Myc, cyclin E, Notch and c‐Jun. FBXW7 is a known tumor‐suppressor gene, and mutations in FBXW7 have been reported in various human malignancies. In this study, we examined the sequences of the FBXW7 and p53 genes in 57 ovarian cancer clinical samples. Interestingly, we found no FBXW7 mutations associated with amino acid changes. We also investigated FBXW7 expression levels in 126 epithelial ovarian tumors. FBXW7 expression was negatively correlated with the malignant potential of ovarian tumors. That is to say, FBXW7 expression levels in ovarian cancer samples were significantly lower than those in borderline and benign tumors ( P < 0.01). FBXW7 expression levels in serous carcinoma samples were the lowest among four major histological subtypes. In addition, p53 ‐mutated ovarian cancer samples showed significantly lower levels of FBXW7 expression compared with p53 wild‐type cancer samples ( P < 0.001). DNA methylation arrays and bisulfite PCR sequencing experiments revealed that 5′‐upstream regions of FBXW7 gene in p53 ‐mutated samples were significantly higher methylated compared with those in p53 wild‐type samples ( P < 0.01). This data indicates that p53 mutations might suppress FBXW7 expression through DNA hypermethylation of FBXW7 5′‐upstream regions. Thus, FBXW7 expression was downregulated in ovarian cancers, and was associated with p53 mutations and the DNA methylation status of the 5′‐upstream regions of FBXW7 . Abstract : FBXW7 is a known tumor‐suppressor gene, and mutations in FBXW7 have been reported in various human malignancies. In this study, we found that the expression level of FBXW7 was correlated with the malignant potential of epithelial ovarian tumor other than mutational status of FBXW7 . This is the first report that FBXW7 expression was downregulated in ovarian cancer and that p53 mutational status had an impact on the DNA methylation status of the 5′‐upstream regions of FBXW7 .